2021
DOI: 10.1371/journal.pmed.1003674
|View full text |Cite
|
Sign up to set email alerts
|

Multi-morbidity and blood pressure trajectories in hypertensive patients: A multiple landmark cohort study

Abstract: Background Our knowledge of how to better manage elevated blood pressure (BP) in the presence of comorbidities is limited, in part due to exclusion or underrepresentation of patients with multiple chronic conditions from major clinical trials. We aimed to investigate the burden and types of comorbidities in patients with hypertension and to assess how such comorbidities and other variables affect BP levels over time. Methods and findings In this multiple landmark cohort study, we used linked electronic healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Our study findings are consistent with Danish and UK studies which showed a positive association between comorbidity and hypertension control. [30,35,36] Patients with comorbidity may have higher risk perceptions of cardiovascular diseases compared to those without comorbidity. [37,38] These patients may be motivated to engage in healthy behaviours and comply with management regimens that are essential for controlling their hypertension than their counterparts without comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Our study findings are consistent with Danish and UK studies which showed a positive association between comorbidity and hypertension control. [30,35,36] Patients with comorbidity may have higher risk perceptions of cardiovascular diseases compared to those without comorbidity. [37,38] These patients may be motivated to engage in healthy behaviours and comply with management regimens that are essential for controlling their hypertension than their counterparts without comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, SBP recordings are often known to be susceptible to measurement error; however, as suggested by previous research, summary measures using averaging are a validated method of alleviating distorted conclusions due to measurement error issues. 15 , 16 Fifth, more precise time-to-event modelling of the outcome and patient censoring are necessary for association analyses. However, because survival DL modelling has not been appropriately developed for association estimation, nuanced evaluation of risk with time-to-event DL modelling should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Potential confounders were identified based on existing literature rather than deferring to statistical criteria ( 23 , 24 ). We assessed demographic characteristics, socio-economic status, lifestyle behavior change, and health status ( 25 , 26 ), which were reported from face-to-face interviews during each follow-up survey. Demographic characteristics and socio-economic variables included sex (male/female), ethnicity (Han nationality/others), average household income (<5,000/5,000–19,999/>20,000 yuan), place of residence (city/town/rural), main occupation before retired (professional and technical personnel governmental/institutional or managerial personnel/agriculture, forest, animal husbandry/fishery worker/industrial worker/ commercial or service worker/military personnel/housework/others), marriage status (currently married and living with spouse/separated/divorced/widowed/never married).…”
Section: Methodsmentioning
confidence: 99%